Numerical and experimental investigation of vibro-acoustic characteristics of a submerged stiffened cylindrical shell excited by a mechanical force. (1st April 2022) - Gao, Cong; Zhang, Hang; Li, Haichao; Pang, Fuzhen; Wang, Hongfu
Abstract: In this paper, the direct testing method is adopted to measure the underwater vibration and sound radiation of a typical stiffened cylindrical shell structure under broadband excitation. The accuracy of the test result is verified by comparing with those obtained by numerical finite element (FE)/boundary element (BE) coupling method. In addition, the free vibration, forced vibration and sound radiation characteristics of stiffened submerged cylindrical shell are presented. The testing procedures and operation steps are established to provide support for the control of the vibration and sound radiation for underwater vehicle in this study. The results show that the trend of test result curve is in good agreement with FE/BE coupling method result, however, the acceleration and sound pressure is slightly different at the resonance peak value between experimental and numerical result in 500–2500 Hz band. In addition, the high frequency vibration and sound radiation response of the structure are mainly caused by a mechanical force. Highlights: The experimental test and numerical comparative study of the vibration and sound radiation of structure are carried out. The testing procedures for underwater vibration and sound radiation of cylindrical shell are established and formed. The free, forced vibration and sound radiation characteristics of stiffened submerged cylindrical shell are studied.